2021
DOI: 10.3348/kjr.2021.0244
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Adequacy and Safety of Percutaneous Transthoracic Needle Biopsy for Molecular Analysis in Non-Small Cell Lung Cancer: A Systematic Review and Meta-analysis

Abstract: Objective We conducted a systematic review and meta-analysis of the tissue adequacy and complication rates of percutaneous transthoracic needle biopsy (PTNB) for molecular analysis in patients with non-small cell lung cancer (NSCLC). Materials and Methods We performed a literature search of the OVID-MEDLINE and Embase databases to identify original studies on the tissue adequacy and complication rates of PTNB for molecular analysis in patients with NSCLC published betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Both pulmonary hemorrhage and pneumothorax in rebiopsy were accepted, and pneumothorax was the most common. Also, a meta-analysis ( 30 ) showed a slight but non-significant reduction in the pooled complication rate for the rebiopsies vs. the initial biopsies (16.8% vs. 22.2%). Although patients showed disease progression after receiving a previous systemic treatment, the overall complication rate of the biopsy was not statistically significant between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Both pulmonary hemorrhage and pneumothorax in rebiopsy were accepted, and pneumothorax was the most common. Also, a meta-analysis ( 30 ) showed a slight but non-significant reduction in the pooled complication rate for the rebiopsies vs. the initial biopsies (16.8% vs. 22.2%). Although patients showed disease progression after receiving a previous systemic treatment, the overall complication rate of the biopsy was not statistically significant between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…16 The association of age and comorbidity score in the current study is consistent with the literature, which reports greater complication rates and reduced health-related quality of life in elderly or medically unfit patients who undergo invasive diagnostic procedures or upfront surgical resection for NSCLC. [17][18][19] A retrospective review of 2,493 patients with lung cancer demonstrated that tissue diagnosis had no significant impact on overall survival or treatment in patients with a higher burden of medical comorbidities or poorer functional status. Moreover, within this subgroup of medically high-risk patients, there was no significant difference in mortality between those who did or did not undergo formal tissue diagnosis.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Over the past few decades, image-guided percutaneous needle biopsy (PNB) for the lung has emerged as the preferred procedure for lung cancer diagnosis [1,2]. Compared to transbronchial or surgical biopsy, PNB under CT, US, and fluoroscopy guidance can be performed easily under local anesthesia, without the need for general anesthesia [3][4][5][6]. PNB for the lung has limitations due to the potential risk of pneumothorax in approximately 15-38% of patients, with a subsequent requirement for chest tube insertion in approximately 5-10% of patients [3,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to transbronchial or surgical biopsy, PNB under CT, US, and fluoroscopy guidance can be performed easily under local anesthesia, without the need for general anesthesia [3][4][5][6]. PNB for the lung has limitations due to the potential risk of pneumothorax in approximately 15-38% of patients, with a subsequent requirement for chest tube insertion in approximately 5-10% of patients [3,5,7]. To avoid the risks of pneumothorax and chest tube placement, a histopathological diagnosis has been obtained through PNB for metastasis involving the pleura, lymph nodes, bones, and solid organs other than the lung [4,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%